Green Beauty: Analysis Of Environmentally Friendly Skincare Product Purchase Decisions - Hanum Nilasari; Alldila Nadhira Ayu Setyaning (Cita konsultindo, 2024)
Global warming and skincare have a significant relationship. One of the impacts of climate change is increasing temperature and extreme weather, which has an impact on skin health. Skincare is a series of activities that support skin health, improve appearance and relieve facial skin conditions. Increasing awareness of environmental issues has encouraged the skincare industry to create more sustainable and environmentally friendly products. This study aims to explore the relationship between eco-friendly skincare products and global warming issues, as well as their contribution to environmental protection. The approach in this study is a quantitative approach. The data collection technique was by distributing online questionnaires to 260 respondents via Google Forms. The sampling technique used is non-probability sampling with purposive sampling method, which will then be processed using structural equation modeling SEM (Structural Equation Modeling) with the help of PLS software. This study found that green perceived value has a positive and significant effect on green trust, green trust has a significant effect on green purchase intention, green perceived value has a significant effect on green purchase intention, and green perceived risk has a significant effect on green purchase intention. This study revealed that perceived risk does not have a significant effect on green trust.